2007
DOI: 10.1128/aem.01139-06
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Influenza A Virus on Copper versus Stainless Steel Surfaces

Abstract: Influenza A virus particles (2 × 106) were inoculated onto copper or stainless steel and incubated at 22°C at 50 to 60% relative humidity. Infectivity of survivors was determined by utilizing a defined monolayer with fluorescent microscopy analysis. After incubation for 24 h on stainless steel, 500,000 virus particles were still infectious. After incubation for 6 h on copper, only 500 particles were active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
230
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(240 citation statements)
references
References 13 publications
4
230
3
3
Order By: Relevance
“…The virus could be easily transferred from contaminated PPE to the skin when the PPE is removed from healthcare workers,10 which may greatly increase the risk of contact transmission. It has also been documented that influenza virus can survive on a wide variety of surfaces including non‐woven fabrics 11, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…The virus could be easily transferred from contaminated PPE to the skin when the PPE is removed from healthcare workers,10 which may greatly increase the risk of contact transmission. It has also been documented that influenza virus can survive on a wide variety of surfaces including non‐woven fabrics 11, 12, 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…1) It has been reported that copper surface can effectively eliminate Methicillinresistant Staphylococcus aureus (MRSA), Influenza A (H1N1) and Escherichia coli-DH5 (E. coli) within a few hours, [2][3][4][5][6][7][8][9] so copper surface can be ideal to be applied in a hospital environment to decrease the chance of transmission of bacteria. The surface of copper metal can be thermally passivated to reflect light and present various color observed by human eyes for decorative purposes 10,11) and interior design.…”
Section: Introductionmentioning
confidence: 99%
“…The use of biocidal surfaces may play a role in preventing infection transmission from contaminated surfaces when combined with stringent cleaning regimes. Laboratory studies have suggested that copper surfaces may be effective against a range of bacteria, fungi, and viruses (8)(9)(10)(11) and that the irreversible pathogen nucleic acid destruction observed may allay fears of biocide resistance (12). A previous study observed that strains of MRSA were killed on copper surfaces in simulated wet-droplet contamination (13).…”
mentioning
confidence: 99%